Emotion Socialization in Teacher-Child Interaction: Teachers’ Responses to Children’s Negative Emotions - Cekaite, Asta; Ekström, Anna (Frontiers in Psychology, 2019)
The present study examines 1- to 5-year-old children’s emotion socialization in an early childhood educational setting (a preschool) in Sweden. Specifically, it examines social situations where teachers respond to children’s negative emotional expressions and negatively emotionally charged social acts, characterized by anger, irritation and distress. Data consist of 14 hours of video observations of daily activities, recorded in a public Swedish preschool, located in a suburban middle-class area and include 35 children and five preschool teachers. By adopting a sociocultural perspective on children’s development and socialization, the study examines the communicative practices through which the expressions of negative emotions are responded to and the norms and values that are communicated through these practices. The data are analysed by using multimodal analysis of interaction that provides a tool for detailed analysis of participants’ verbal and embodied actions and sense-making. The analyses show that teachers responded to children’s negatively charged emotional expressions as social acts (that were normatively evaluated) and the adults instructed children how to modify their social conduct (rather than deploying explicit discussions about emotions). The teachers used communicative genres that prioritized general moral principles and implemented the non-negotiability of norms over individual children’s emotional-volitional perspectives and individual preferences. The teachers’ instructive socializing activities were characterized by movement between multiple temporal horizons, i.e., general (emotional) discourse that transcended the here-and-now, and specific instructions targeting the children’s conduct in a current situation. The study discusses how emotion socialization can be related to the institutional characteristics and collective participatory social conditions of early childhood education.